ESBL-producing enterobacteriaceae-related urinary tract infections in kidney transplant recipients: incidence and risk factors for recurrence. Issue 10 (October 2015) - Pilmis, Benoît; Scemla, Anne; Join-Lambert, Olivier; Mamzer, Marie-France; Lortholary, Oliver; Legendre, Christophe; Zahar, Jean-Ralph
Abstract: Background: Urinary tract infections (UTIs) represent the first cause of bacterial infections in renal transplant recipients. In a period of increasing resistance to antimicrobial agents, the factors leading to the development of UTI in previously urinary colonized renal transplant recipients as well as the factors associated with recurrence of UTIs have to be determined. The aims of this retrospective study were (1) to assess the incidence of extended-spectrum beta-lactamase-producing enterobacteriaceae (ESBL-PE)-related UTI in kidney transplant recipients, (2) to identify factors associated with ESBL-PE infection and (3) to determine the risk factors for recurrence. Methods: We included all kidney transplant recipients admitted in our hospital between January 2009 and January 2012 who had a monobacterial ESBL-PE UTI or bacteriuria. Results: During the study period, 659 patients underwent kidney transplantation; 72 patients had ESBL-PE bacteriuria, representing a 10.9% prevalence, and among the latter 34 (47.2%) presented an ESBL-PE-related UTI. Fourteen patients (41.2%) experienced a UTI relapse associated with two factors: advanced age ( p = 0.032) and persistent bacteriuria 48 h after appropriate antibiotic therapy ( p = 0.04). No other risk factor for recurrence was found, including the presence and management of a ureteral stent during the first UTI, causative microorganisms, or diabetes mellitus. Conclusions: In this specific population, regarding the risk of relapse there is an urgent need for prospective studies to test the best treatment strategy.